2013
DOI: 10.1080/09593330.2013.786103
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate removal from aqueous solutions by nanoscale zero-valent iron

Abstract: In this study, nanoscale zero-valent iron (NZVI) was synthesized by conventional liquid-phase chemical reduction methods without a support material and then characterized by transmission electron microscopy (TEM), scanning electron microscopy (SEM) and X-ray diffraction (XRD). The effect of NZVI particles on phosphate removal from aqueous solutions was examined. The results showed that the phosphate removal efficiency increased from 34.49% to 87.01% as the dosage of nanoscale iron particles increased from 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(22 citation statements)
references
References 35 publications
4
18
0
Order By: Relevance
“…On the contrary, with the exception of PFOA, further increase of nZVI concentration from 100 to 1000 mg L -1 did not significantly affect PFCs removal. A similar trend was also observed in a previous study [36], where Wu et al observed no significant difference on removal of other anions (phosphate) with increase of nZVI concentration from 400 to 600 mg L -1 . …”
Section: Effect Of Nzvi Concentration On Pfcs Removalsupporting
confidence: 73%
“…On the contrary, with the exception of PFOA, further increase of nZVI concentration from 100 to 1000 mg L -1 did not significantly affect PFCs removal. A similar trend was also observed in a previous study [36], where Wu et al observed no significant difference on removal of other anions (phosphate) with increase of nZVI concentration from 400 to 600 mg L -1 . …”
Section: Effect Of Nzvi Concentration On Pfcs Removalsupporting
confidence: 73%
“…Compared with chemical precipitation, adsorption does not produce large volumes of chemical sludge. Various types of phosphorus adsorbents made from zeolites [46], lanthanum and yttrium compounds [47,48], aluminum compounds [49, 50,51,52,53], zero-valent iron [54], amine-functionalize, Pr(OH)3 [55], magnesium amorphous calcium carbonate [56], zirconium compounds [57,58], and iron(III) oxide compounds [12,30,31,38,40,51,59,60,61] were studied.…”
mentioning
confidence: 99%
“…Therefore, providing a surface coating of a thin layer of Fe 3 O 4 [22], could alleviate this problem, thereby enhancing the reactivity of ZVINPs. The removal of PO 4 3-from aqueous solution by ZVINPs takes place by simultaneous adsorption and chemical precipitation [23]. Initial pH of solution and point of zero charge (PZC) of adsorbent are very important parameters that affect the adsorption of cationic and anionic species on a solid-liquid interface.…”
Section: Removal Mechanismmentioning
confidence: 99%